Síntese de isósteros aromáticos visando potencial biológico - SILVEIRA, Viviane Aparecida da (2016)
The goal of this research deals with the synthesis and characterization of a series of pyridinic isosteres, which were evaluated in the anti-Trypanosoma cruzi assays. These compounds were designed using isosterism and bioisosterism strategies. The compounds 16, 17, 18, 20, 21, 22, 23, 24, 25 and 26 were synthesized by nucleophilic aromatic substitution reaction (SNAr), using as nucleophiles: ethyl glycinate hydrochloride, ethyl thioglycolate and ethyl glycolate; and substrates: 2,6- dichloro-3-nitropyridine, 2-chloro-3-nitropyridine and 1-chloro-2-nitropyridine. The products (17, 18, 21, 22, 23, 25, 26) were submitted to the reduction reaction of nitro to amino group using metallic iron (Feº), and ammonium chloride (NH4Cl). In the sequence the intramolecular reaction led to the formation of cyclized products 29, 30, 31, 32 and 34. The compounds were characterized by nuclear magnetic resonance, electrospray ionization mass spectrometry and infrared spectroscopy. From the mass spectra of compounds 17, 18, 21, 22, 24 and 26, it was possible establish a general fragmentation, and the oxygenated derivative showed, in addition to that standard, additional fragments, which contributes to confirm the synthesis of these products. After the characterization of the compounds (18, 21, 22, 23, 26, 29, 31 and 34) tests for the evaluation of cytotoxicity and anti-Trypanosoma cruzi activity were performed. The anti-Trypanosoma cruzi activity (IC50) of the compounds was evaluated against CL Brener strain of T. cruzi and neither of the compounds showed anti-Trypanosoma cruzi activity. Cytotoxicity was determined using strains of LLC-MK2 cells. According with the CC50 values observed in this model and the concentrations evaluated, it was possible conclude that the products did not shown cytotoxicity.